Ultrafast electron energy-loss spectroscopy in transmission electron microscopy. (10th July 2018) - Pomarico, Enrico; Kim, Ye-Jin; García de Abajo, F. Javier; Kwon, Oh-Hoon; Carbone, Fabrizio; van der Veen, Renske M.
Abstract: Abstract : In the quest for dynamic multimodal probing of a material's structure and functionality, it is critical to be able to quantify the chemical state on the atomic-/nanoscale using element-specific electronic and structurally sensitive tools such as electron energy-loss spectroscopy (EELS). Ultrafast EELS, with combined energy, time, and spatial resolution in a transmission electron microscope, has recently enabled transformative studies of photoexcited nanostructure evolution and mapping of evanescent electromagnetic fields. This article aims to describe state-of-the-art experimental techniques in this emerging field and its major uses and future applications.